A New Strategy of Discretionarily Reconfigurable Actuators Based on Self‐Healing Elastomers for Diverse Soft Robots. (20th January 2021) - Lou, Jiaming; Liu, Zenghe; Yang, Lei; Guo, Yifan; Lei, Dong; You, Zhengwei
Abstract: Actuators have shown great promise in many fields including soft robotics. Since reconfiguration allows actuators to change their actuation mode, it is considered a key characteristic for new‐generation adaptive actuators. However, it remains a challenge to design simple and universal methods to fabricate actuators that can be reconfigured to allow diverse actuation modes. Here, a macroscopically discretionary healing‐assembly strategy to fabricate reconfigurable soft actuators based on intrinsic self‐healing poly(dimethylglyoxime‐urethane) (PDOU) elastomers is developed. The PDOU elastomers with different degrees of crosslinking show different responsiveness to solvents, and are seamlessly healed. Crosslinked and non‐crosslinked PDOU elastomers as building units are healing‐assembled into actuators/robots with diverse actuation behaviors. Notably, the assembled actuators/robots are readily reprogrammed to exhibit multiple actuation modes by simply tailoring and reassembling without any external stimuli. This work paves a new, simple, powerful, and universal method to construct sophisticated soft robots. Abstract : Based on common dynamic bonds, polyurethanes with different solvent‐responsiveness are seamlessly healed into an actuator at room temperature. Through disassembly and reassembly of self‐healing building units, multiple reconfigurable actuations are easily obtained from a single actuator without stimuli. This strategy develops a pioneering application of self‐healing materials and presents a simple and powerful method to design and fabricate soft robots.